The functional network of ion channels in T lymphocytes - Cahalan, Michael D. (2009)
For more than 25 years, it has been widely appreciated that Ca(2+) influx is essential to trigger T-lymphocyte activation. Patch clamp analysis, molecular identification, and functional studies using blockers and genetic manipulation have shown that a unique contingent of ion channels orchestrates the initiation, intensity, and duration of the Ca(2+) signal. Five distinct types of ion channels – Kv1.3, KCa3.1, Orai1+ stromal interacting molecule 1 (STIM1) [Ca(2+)-release activating Ca(2+) (CRAC) channel], TRPM7, and Cl(swell) – comprise a network that performs functions vital for ongoing cellular homeostasis and for T-cell activation, offering potential targets for immunomodulation. Most recently, the roles of STIM1 and Orai1 have been revealed in triggering and forming the CRAC channel following T-cell receptor engagement. Kv1.3, KCa3.1, STIM1, and Orai1 have been found to cluster at the immunological synapse following contact with an antigen-presenting cell; we discuss how channels at the synapse might function to modulate local signaling. Immuno-imaging approaches are beginning to shed light on ion channel function in vivo. Importantly, the expression pattern of Ca(2+) and K(+) channels and hence the functional network can adapt depending upon the state of differentiation and activation, and this allows for different stages of an immune response to be targeted specifically.